HUBUNGAN SOPAN SANTUN BERPAKAIAN DENGAN NILAI KESOPANAN SISWA DI LINGKUNGAN SEKOLAH MENENGAH ATAS DI KOTA DEPOK - Nafis, Wildan; Sauvika, Farah (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to examine the relationship between clothing etiquette and students' politeness values in high school environments in Depok City. Using a quantitative approach with a correlational design, this research collected data through questionnaires completed by 80 students from a population of 100 students. The results show a significant and positive relationship between clothing etiquette and students' politeness values, with a significance value of 0.000 (less than 0.005), and a strong relationship with a Pearson correlation coefficient of 0.879. These findings indicate that the higher the students' compliance with dress code rules, the higher the politeness values they demonstrate in school.